Epidermal growth factor receptor-targeted poly(amidoamine)-based dendrimer complexed oncolytic adenovirus: is it safe totally? - Huang, Min; Yang, Chun-Sheng; Xin, Yong; Jiang, Guan (Journal of Thoracic Disease; Vol 9, No 1 (January 24, 2017): Journal of Thoracic Disease, 2017)
Oncolytic adenoviruses (OAds) express shRNA (1) and selectively replicate in and lyse cancer cells. Therefore, they are commonly used as vectors in clinical trials for cancer gene therapy (2). However, because the oncolytic antitumor activity is insufficient to effectively eliminate tumors, “armed” (e.g., polymers, liposomes, or nanoparticles) oAd have been devised to extend the circulation time, reduce immunogenicity, and result in an increased antitumor effect, as well as lower the accumulation and toxicity in the liver (3). To overcome the non-specificity of conventional chemotherapeutics, an epidermal growth factor receptor (EGFR) inhibitor, Erbitux (ErbB), was developed as a well-documented and efficacious antibody against EGFR (4), and is now widely used to treat lung cancer patients (5).